Enhanced electrochemical performance by a three-dimensional interconnected porous nitrogen-doped graphene/carbonized polypyrrole composite for lithium–sulfur batteries. Issue 31 (10th March 2016) - Zhang, Fei-Fei; Wang, Chun-Li; Huang, Gang; Yin, Dong-Ming; Wang, Li-Min
Abstract : 3D interconnected porous nitrogen-doped graphene/carbonized polypyrrole nanotubes are employed as sulfur hosts, they exhibit excellent electrochemical performance for lithium–sulfur batteries. Abstract : Three-dimensional interconnected porous nitrogen-doped graphene/carbonized polypyrrole nanotube (N-GP/CPN) materials have been fabricated via carbonization and chemical activation of polypyrrole-functionalized graphene nanosheets with KOH. The obtained N-GP/CPN with high surface, abundant nanopores and nitrogen doping can serve as conductive substrates for hosting a high content of sulfur and can effectively impede the dissolution of polysulfides. The N-GP/CPN-S composite exhibits excellent electrochemical performance as the cathode material for lithium–sulfur (Li–S) batteries, including a high initial discharge capacity of 1128 mA h g −1 at 0.5C, a notable cycling stability with a high stable capacity of 726 mA h g −1 and an ultraslow decay rate of 0.07% per cycle as long as 500 cycles. Moreover, the N-GP/CPN-S cathode also exhibits good rate capacity, showing a high reversible stable capacity of 687 mA h g −1 at 4C.